A study of critical thinking skills among Thai dental students: From disposition to skills assessment - Kittichai Sireerat; Naoko Seki; Richard Foxton; Shin-Ru Liao; Masako Akiyama; Supaporn Sangouam; Ikuko Morio (Journal of Dental Sciences, 2025)
Background/purpose: Critical thinking skills might be influenced by culture. There has been no published research to date, on the critical thinking skills of Asian undergraduate students and so this study's purpose was to explore the critical thinking skills of Thai undergraduate dental students to elucidate their level and whether there might be need for training to improve their critical thinking. Materials and methods: Participants were second- (n = 63) and fifth-year (n = 51) undergraduate dental students in the 2023 academic year at Naresuan University, Thailand. A questionnaire was distributed, which included questions on demographic information and a Thai version of the California Critical Thinking Skills Test (CCTST). Results: The response rate was 100 % and the overall mean CCTST score of the students was 15.34 (SD 3.6). There were no statistically significant differences between the two years (P > 0.05), and “Induction” was not manifested. There was no significant correlation between GPA and all the domains of the CCTST scores; however, there was a significant correlation between students’ frequency of critical thinking use and overall CCTST score (P = 0.047, ρ = 0.187) and what students thought about the importance of critical thinking and their frequency of critical thinking use (P < 0.01, ρ = 0.337). Conclusion: The critical thinking skills scores of all the undergraduate Thai dental students were found to be moderate indicating a need for interventions aimed at improving all the domains of critical thinking skills in particular the domain of “Induction” in the undergraduate curriculum.